Strengthening Spirituality Through Tazkiyatun Nafs in Islamic Broadcasting Communication: A Case Study of a Virtual Da’wah Program - Iin Indrawati Budi Utami; Indra Martian Permana; Nirwan Syafrin (STAI Publisistik Thawalib Jakarta, 2026)
This study arises from the observation that digital da’wah communication remains predominantly oriented toward information dissemination and has not been fully effective in fostering spirituality, encouraging self-transformation, and strengthening audiences' faith in the digital era. This study aims to analyze the internalization of Tazkiyatun Nafs, the communication strategies implemented, and the spiritual impacts of a virtual da’wah program on the behavioral changes of active participants. The study employed a qualitative approach using a single case study method involving six informants, speakers, and hosts through in-depth interviews, participant observation, documentation, and data analysis following the Miles and Huberman model with source and technique triangulation. The findings indicate that the virtual da’wah program based on Tazkiyatun Nafs functions not only as a medium for disseminating knowledge but also as a form of Islamic psychological therapy and self-transformation. Structured riyadhah practices helped participants connect intellectual religious understanding with profound spiritual experiences. Participants experienced increased self-awareness, emotional control, discipline in worship, and positive behavioral changes. Communicative interactions among speakers, hosts, and audiences created a continuous process of value internalization. The findings produced a transformative communication model based on tasawuf that integrates cognitive, emotional, and psycho-spiritual aspects within digital da’wah, strengthening participants’ faith and reducing the spiritual emptiness experienced by modern society. In conclusion, Tazkiyatun Nafs in digital da’wah effectively strengthens spirituality, encourages self-transformation, and develops more transformative and sustainable Islamic communication. This study contributes to the development of a tasawuf-based digital da’wah communication model to strengthen spirituality and support society's psychosocial transformation in the modern era.